ANALISIS WACANA PADA PIDATO KING GEORGE VI â€œWith Godâ€™s Help, We shall Prevailâ€. (First Radio Address, Britania. September 3, 1939). - SARIRA, MARISKA ROSSY (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT Â This skripsiwas made as a requirement to obtain bachelor Degree in English in Sam Ratulangi University. This research is entitled â€œDiscourse analysis of King George VI Speechâ€With Godâ€™s Help, We shall Prevailâ€(First Radio Address, Britania. September 3, 1939)â€. It is an attempt to analyze and explain the discourse analysis norms in King George VI speech. There are three steps to finish this research. First step is preparation,the writer reads some books about language, linguistics, and discourse analysis to find out the relevant theories.Second step is data collection, the writer finds King George VI speech and reads it for several times to have a deep understanding. Third step is data analysis,The data arecollected, identified, classified and analyzed. The method used in this research is taken from Alba-Juez (2008:20) and supported the theory by De Beaugrande and Dressler (1986:8) and Aarts and Aarts (1982: 4). The theory consists of seven norms, they are: Cohesion: pronoun, substitution, ellipsis, conjunction, lexical, Coherence: mark coherence, and unmark coherence, Intentionality, Acceptability, Informatifity, Situationality, and Intertextuality. The result of this research shows that in cohesion there are 50 pronouns, 7 subtitusion, no elipsis, 34 conjuction, 10 lexical. In this speech, there are 21 mark coherence and there is no unmark coherence. There are also the norms like intentionality is focused on user or producer by expressing a disappointment and sadness. Acceptabilityhas a generally acceptable meaning, according to the history of the text of this speech is received, the king get a warm welcome from the people and members of the royal. Informatifity is can provide full information,can be known through historical conditions occurred. Situationalityhas a relationship with the surrounding circumstances, refers to the situation of war. And intertextualityrefer to the agreement as a protector of the independence of Poland. Keywords: discourse analysis, speech, seven norms, King George VI